“Locked” Scapholunate Instability Diagnosed with 4D Computed Tomography Scan - Bain, Gregory I.; Krishna, Sathya Vamsi; MacLean, Simon; Carr, Renee; Slavotinek, John (Journal of Wrist Surgery, 2019)
Background Scapholunate instability (SLI) has a wide range of clinical and radiological presentations. The management depends on the stage of the disorder. Subluxation of scaphoid is pathognomonic feature of the SLI. We describe a patient with SLI with a dislocated proximal pole of scaphoid, out of the distal radius scaphoid fossa. The 4D (three-dimensions + time) computed tomography (CT) scan demonstrated that the scaphoid did not reduce throughout wrist motion.Case Description A 20-year-old male presented with SLI following a fall skateboarding. The 4D CT scan revealed the dislocated scaphoid that did not reduce with wrist motion. He underwent open reduction of the proximal pole of scaphoid and SL reconstruction using flexor carpi radialis (FCR) tendon graft with the Quad tenodesis technique. At 1 year, he had improved pain, wrist functions, and maintained satisfactory radiological alignment.Literature Review We are not aware of any previous description of the dorsal scaphoid dislocation in association with scapolunate instability.Clinical Relevance We recommend that the SLI staging classification needs to be expanded to include dislocation (locked) stage. The 4D CT has a significant role in identifying the instability and its reducibility.Level of Evidence This is a level V study.
Keywords: scapholunate instability; locked scapholunate instability; scaphoid dislocation; carpal; instability; 4D CT scan